Walking the First/Last Mile to/from Transit: Placemaking a Key Determinant - Chidambara, (2019)
Sustainable mobility concerns have seen cities introducing mass transit systems, but travel choice factors such as accessibility, convenience, comfort and safety cannot be addressed through a transit system alone. A trip made on a transit system requires commuters to utilise more than one mode of transport. Walking is generally the most common transport mode to access and egress transit stops. While there is evidence on the pedestrian environment influencing transit ridership, only a few studies have explored how it affects the share of people who walk to/from transits, especially in the context of the developing world. This article postulates that the pedestrian environment influences users’ decision to walk the last mile, substantiating it with the findings of a study of transit users across the metro stations of Delhi, India. A pedestrian environment index is developed by including elements of the built form and activities adjacent to the network of streets, in addition to the pedestrian infrastructure quality. Interestingly, the route environment is found to have a significant and much higher correlation with walk share in contrast to pedestrian infrastructure availability. Within the route environment, the sub-indicator that impacts walk share the most is placemaking. It highlights the significance of planning for an enhanced pedestrian environment in a larger context of the catchment area, in contrast to the current myopic approach of station-centric pedestrian infrastructure provisioning.